Educational Effects of SW Coding Notes on Computational Thinking (International journal of recent technology and engineering, 2019)
Computational thinking is a fundamental skill to be used by everyone in the 4th industrial revolution age and it is a hot issue of the education field in the world. Usually, SW coding means the whole process to make a computer program. Since a program has logical structure and its development process requires subsidiary abilities which analyze a problem and devise the stepwise procedure, SW coding has been understood to be a good method for computational thinking(CT). In this paper, we propose a way to teach CT by using coding notes and analyze its educational effects on CT. To find the educational effects of SW coding notes, logical reasoning ability before and after SW coding education was measured through questionnaire survey and compared by statistical methods. We sampled 51 students and divided them two groups; one for computer science major(38) and the other for computer science non-major(13). They are asked to answer three categories of questions such as problem understanding, data analysis, and problem solving. An d then by the paired t-test along with normality and homoscedasticity of two groups, the change of student’s CT ability before and after taking SW coding education was statistically tested at a significant level of 95%. According to our experiments, p-values of the paired t-test for problem understanding, data analysis, and problem solving are 0.176, 0.134, and 0.470, respectively and alternative hypotheses are accepted. It implies that student’s logical reasoning ability can be improved and their academic achievement is also relatively great by using SW coding notes. Although there are similar results for educational effects of SW coding, our work is different from them in terms of using new education tool named as SW coding notes.